Reconciling the cognitive and social approaches to describing teacher talk in second language classrooms: The contribution of systemic functional linguistics - Xie, Min; Tu, Binglan (Frontiers in Communication, 2023)
Teacher talk plays an important role in second language classroom interaction. Studies are informed by multiple theories and yet could be classified under two general approaches, i.e., cognitive and social. The two approaches provide different but complementary perspectives for the role of teacher talk in interaction, with a focus on either learners’ cognitive change or their social participation. A conversation between them is called for in the academic field to understand their interdependent relationship as well as the loss and gain in the respective approach. However, the conversation is difficult to launch because the cognitive and social approach have developed distinct perspectives on what constitutes language and how learning evolves, leading to seemingly incompatible descriptive paradigms. With reference to Systemic Functional Linguistics (SFL), this paper argues for reconciling the two approaches in the following aspects. Firstly, the meaning-oriented view of language in SFL expands the learning scope beyond language forms and offers both approaches an angle to reconsider the focus of interaction. Secondly, the semiotic view of learning in SFL blurs the boundary of cognition and language use and provides a perspective for understanding the mediated role of language in the cognitive and social process of learning. Finally, the functions of scaffolding in teacher talk revealed by SFL based on a linguistic analysis might not only enrich the description in each approach, but also enable findings across the two approaches to be comparable. It is anticipated that SFL would create new spaces for the conversation between the two approaches.